From Fear to Understanding: Millennials’ Perceptions of Islam in Contemporary Society as a Basis for Interfaith Dialogue and Cooperation - Akmad, Saiden Panggo; Espacio, Nancy B. (Future Science / FSH-PH Publications, 2024)
This study aimed to describe the millennials' perception of Islam in contemporary society as a basis for interfaith dialogue and cooperation. A descriptive research method was utilized. Respondents were selected using stratified probability sampling. A total of 255 were used primarily as the respondents of this study. The data gathered were analyzed using the SPSS software V21x64. The statistical methods used were frequency and percentage counts, standard deviation, mean, and the grand mean. The respondents’ demographic profile relative to age, the 25-28 age group had more respondents than other age groups. As to sex, females dominated the number of respondents. In terms of tribe, most respondents are Cebuano. Regarding religious affiliation, Roman Catholics have a significant number of respondents and in educational attainment, most of the respondents are high school graduates. Millennials with a moderately high perception of Islam view the religious practices of Islam in a positive light. They may appreciate the emphasis on prayer, fasting, and charity as acts of devotion. Regarding cultural aspects of Islam, millennials with moderately high perceptions may appreciate the rich history and traditions associated with Islamic culture. Relative to governance, millennials with moderately high perceptions may acknowledge the influence of Islamic principles in shaping societies governed by law. They may recognize the importance of justice, fairness, and social welfare in Islamic governance systems and appreciate the emphasis on community and public welfare. Millennials with a moderately high perception of Islam will likely have a positive view of it, appreciating its religious practices, cultural contributions, and governance principles. They may also be open to learning more about Islam and engaging in interfaith dialogue and cooperation with practitioners of different religions.